Analisis Perancangan Suply Chain Management Pada PT. Magnesium Gosari Internasional - Setiawan, Kenny; Djazuli, Raden Achmad (Jurnal Ekonomi Pertanian dan Agribisnis, 2024)
Supply Chain Management plays a crucial part in the operations of a company's business organization. Through the implementation of supply chain management, industries can mitigate losses and subsequently increase their profitability. Companies can facilitate the collaboration of stakeholders involved in the conversion of raw resources into finished products. Consequently, the optimization of the production process and distribution of products/services generated by an industry can enhance operational efficiency. Supply chain management involves the identification of suppliers, strategic planning of logistics, and efficient delivery of goods and materials. The objective of this research is to assess the planning of supply chain management (SCM), investigate the process of supplier selection, and analyze logistics distribution. This study employs qualitative methodologies with a descriptive analytic framework that exclusively concentrates on the planning aspect of Supply Chain Management. The findings of this study indicate that the selection of suppliers in companies involves a collaborative effort among multiple agents who contribute essential materials for the production process and supply chain management (SCM). This collaboration encompasses various aspects, such as procurement procedures, data on multiple raw material suppliers, material handling at the warehouse, the production process, supplier distribution to the company, distribution to customers, and logistics transportation. The supply distribution follows a centralized approach, where approved supplies from the industrial warehouse are subsequently distributed to consumers through suppliers who are company partners responsible for distributing the finished products.